Քաղաքական երկխոսության ինստիտուցիոնալացման հիմնախնդիրները ՀՀ-ում - Գալստյան, Խաչիկ (YSU Journal of International Affairs, 2016)
The article discusses the problem of institutionalization of the political dialogue in the Republic of Armenia. In the context of democratic transformation reveals the basic regularities of constitutional construction, institutionalization of political conflicts and dialogical practices, endogenous and exogenous factors of constitutional reforms, as well as new opportunities of institutionalization of the constitutional political dialogue in Armenia.
Keywords: political dialogue, democratic consolidation, institutionalization of the dialogue, constitutional reforms